CORAK PEMIKIRAN HUKUM ISLAM NAHDHATUL ULAMA (NU) - Samani Sya'roni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
In an effort to accommodate the problems faced by the Ummah, especially in legal issues of a case, NU formed an institution known as bahts al- masa'il (the discussion for various issues). The workings of this institution is assumed that the works of fiqh schools become the main guideline in solving legal issue. This correlates closely with the views of NU to the chain of transmission of Islamic science that was allegedly not to be interrupted. Based on that view, when NU wants give legal opinion, it always tries to trace the valid chain in every generation.